Divulgação ambiental corporativa segundo os objetivos de desenvolvimento sustentável: uma abordagem à luz do sistema nacional de negócios - Sobreira, Karoline Rodrigues (2022)
In 2015, the United Nations presented 17 Sustainable Development Goals (SDGs) and 169 related targets that address the global challenges of climate change, social inequality and environmental degradation. Companies can contribute to the achievement of the SDGs, however, there may be differences in their practices and disclosure due to the diversity of expectations and political, financial, economic and social realities of the countries in which they are located. The approach of the National Business System, supported by the Institutional Theory, aims to explain the international differences in the behavior of companies. The study aims to investigate the influence of national institutional factors on corporate disclosure of environmental actions aimed at achieving the SDGs. For this, the environmental disclosure of 839 companies, from 31 countries, from environmentally sensitive sectors, from 2015 to 2019, contained in the Thomson Reuters database was analyzed. Analyzes were performed with descriptive statistics, and regression techniques with panel data. The results show that from 2015 onwards, companies began to disclose more environmental information in their reports. In ddition, it was observed that the most recurrent information in corporate reports was that related to drinking water and sanitation (SDG 6). It was observed that the environmental disclosure of companies related to the SDGs is negatively influenced by the haracteristics of the countries regarding the Control of Corruption and the Quality of Higher Education and Training; providing evidence that in countries with greater control of corruption and with better education systems, companies tend to disclose less. On the other hand, Financial Market Development and Cooperation in Labor Relations exerted a positive influence on environmental disclosure related to the SDGs, indicating that in countries with more developed stock markets and more cooperative labor relations, companies tend to disclose more. The country's Macroeconomic Development did not show a significant influence on this disclosure. Cultural Aspects - Distance from Power and Masculinity x Femininity -, had a negative and significant influence, indicating that companies in environments with less social inequalities and more oriented to femininity disclose more environmental information about the actions taken to achieve the SDGs in their corporate reports. Results related to Aversion to Uncertainty (INC) and Individualism x Collectivism (IND) indicated that in societies that are more individualistic and marked by greater aversion to strategies to face risks and uncertainties, companies tend to disclose more environmental information regarding the SDGs. The findings of the study show how aspects of institutional environments influence companies and their contribution to advances in achieving the goals established in the UN 2030 Agenda, as well as21 provides directions to national authorities to ensure effectiveness in achieving these goals. goals. National aspects are pointed out that can be worked on in order to enable companies to apply and disseminate sustainable environmental practices of action. The dissemination of the theme in the academic environment and in society will make it possible to contribute to the awareness of nations and companies in order to avoid or reduce the imminent risks of climate change.